E0248 Influence of gender on pulse wave velocity and arterial compliance in patients with hypertension and coronary heart disease 1. (17th November 2010) - Hai-qing, Gao; Bao-ying, Li; Xiao-Li, Li; Mei, Cheng; Fei, Yu
Abstract : Objective: The lower incidence of atherosclerosis in premenopausal women than in men was an established epidemiological observation. However, the incidence of cardiovascular disease in women increased dramatically after postmenopausal years. Compliance and distensibility are wall properties of arteries, which may play a role in cardiovascular disease. The purpose of this study was to investigate whether the influence of gender on arterial compliance in patients with hypertension (HP) and/or coronary heart disease (CHD). Methods: The cohort consisted of 500 patients with HP and/or CHD who were registered as outpatients in the Department of Geriatrics of the Qi-Lu Hospital of Shandong University from February 2007 to April 2008 (age from 45 to 87 year). All subjects gave informed written consent. The study protocol was approved by the Ethics Board of Qi-Lu Hospital of Shandong University. Five hundred patients (330 men, 170 women) were divided into four groups: premenopausal women (n=54) and age-matched normotensive men (n=118), postmenopausal women (n=116) and age-matched men (n=212). Postmenopausal women did not receive hormone replacement therapy. Carotid-femoral pulse wave velocity (CF-PWV), capacitive arterial compliance (C1), and oscillatory arterial compliance (C2) were measured using Complior SP automatic device and DO-2020 cardiovascular profiling instrument. Premenopausal and postmenopausal women were compared with age-matched men. Results: Postmenopausal women had lower positive rates of CF-PWV and C1 than age-matched men (44.83% vs 72.17%, p<0.01; 25.86% vs 41.04%, p<0.01), whereas the positive rates of C2 was higher in postmenopausal women (35.34% vs 15.57%, p<0.01). But the positive rates of CF-PWV, C1 and C2 of premenopausal women did not differ significantly than age-matched men (p>0.05). Women with CHD, HP+CHD had lower CF-PWV (p<0.05) than men. CF-PWV of women with HP did not differ significantly than men with HP (p>0.05). Moreover, women with CHD, HP+CHD had lower positive rates of CF-PWV and C1 than men (3.33% vs 36.54%, 3.33% vs 21.15%, p<0.05; 58.11% vs 81.38%, 29.73% vs 50.34%, p<0.01), whereas the positive rates of C2 was higher in women with CHD, HP, HP+CHD (30.00% vs 9.62%, 22.73% vs 9.77%, 32.43% vs 18.62%, p<0.05). But the positive rates of CF-PWV of women with HP did not differ significantly than men with HP (p>0.05). In multiple regression analysis of patients with CHD, HP and CHD, CF-PWV, C1 and C2 were significantly correlated with gender (women) (r=0.480, −0.259, −0.242, p<0.05; 0.200, −0.145, −0.237, p<0.05), whereas there were no close correlations between CF-PWV and gender (women) in the patients with HP (r=0.095, p>0.05). Conclusion: The effect of cardiovascular risk factors on arterial compliance was not uniform but depends on gender and menopause.